Pebbling Number of C_5×C_5×C_5 - Jitendra Binwal; Aakanksha Baber (International Journal of Advanced Science and Technology, 2020)
A graph pebbling is mathematical game play on the vertices of graph with respect to the pebbling steps. The pebbling step is the shifting of two pebbles and attachment of one pebble on the specified arbitary vertex. We propose the pebbling number of where graph is consists of 125 vertices.